Peran Home Industry Dalam Meningkatan Kesejahteraan Keluarga Perpektif Ekonomi Islam (Studi Kasus pada Home industry Mie Telur UD Sarindo Jaya Samarinda) - Kurnia, Feby; Norvedewi, Norvadewi; Chandra, Alias (Borneo Islamic Finance and Economics Journal, 2023)
Feby Kurnia, 2022. "The Role of Home Industry in Improving Family Welfare from an Islamic Economic Perspective (Case study on Egg Noodle Home Industry UD Sarindo Jaya Samarinda). Thesis, Department of Sharia Economics, Faculty of Islamic Economics and Business, State Islamic University of Sultan Aji Muhammad Idris Samarinda. This research was guided by Mrs. Hj. Norvadewi M.Ag. and Mr. Alias ​​​​Candra M.E.I. The background of this research is that the results of Home Industry production are not well known to the general public in Samarinda. No exception for distributors and retailers who trade in the market. Such as the production of raw noodles not many people know. The noodles was made by a couple of home industry entrepreneurs, husband and wife couple Fredi and Emmy on Padat Karya, Street North Sempaja Village, Samarinda. The purpose of this study was to determine the role of UD Sarindo Jaya's home industry in improving the welfare of employees' families in terms of an Islamic economic perspective. In this study, researcher used qualitative research. The research approach used in this study was descriptive qualitative and data collection techniques consist of observation, interviews and documentation. The location in this study is the North Sempaja Village, Samarinda City. The data analysis technique in this study uses the Miles and Huberman models, which consists of data collection, data condensation, data presentation and conclusions. The results of the study, that UD Sarindo Jaya's home industry is a business activity that is able to provide economic services to the community in North Samarinda Village and has a role in improving the community's economy, while also increasing welfare, especially for employee families. In terms of Islamic economic, UD Sarindo Jaya's home industry has been well run and in line with Islamic law, regarding the marketing of production results, researchers did not see any usury, gharar and maisir in marketing carried out by respondents in North Sempaja Village. Marketing is done by distributing goods directly from producers to consumers or agents. So the practice is very simple, that is, the price is received after the goods are delivered. Keywords: The Role of Home industry, Family Welfare an Islamic Perspective.